Urban architectural heritage, not Real Estate - Nguyen Thi Hanh Nguyen; Nguyen Thi Nhu Trang (E3S Web of Conferences, 2023)
Vietnam is one of the fastest urbanizing countries in East Asia. According to September 2022 data, the national urbanization rate has reached about 41.5%, with 888 urban areas [1]. Along with that, real estate prices skyrocketed. As of 2020, the average housing price in the place of the lowest increase is also 3 times higher than in 2011 [2]. Rapid urbanization and rising property prices are two of the many factors that contribute to the difficulty of preserving urban architectural heritage. Owners when faced with the choice of preserving their heritage or “converting the estate” into real estate for sale often lean towards the latter. This theoretical paper aims to test the hypothesis about the first option - conservation of heritage whether there are long-term benefits for the owners as well as the community and society. The study is based on the analysis of changes in the value of urban architectural heritage and real estate over time. Combined with lessons learned on how to deal with heritage from cities around the world, the study raises the view that Urban Architectural Heritage is a form of long-term net-earning asset, not quick-profit Real Estate. The study also emphasizes the factors that create urban identity such as long-standing traditions and differences in urban architecture, which play a key role in helping to reverse the trend of globalization, which is a hot issue of many present urban.